The Influence of Financial Compensation and Work Discipline on Employee Performance PT. Indah Logistik Internasional - Akbar Meidian; Neny Rostiati; Endah Dewi Purnamasari (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine the effect of financial compensation and work discipline on employee performance at PT. Indah International Logistics. The Sample was selected using the saturated sample technique. The data in this study was 50 respondents. Data collection techniques utilized questionnaire. This study utilized multiple linear regression method to analyze the data. The results of the study prove that financial compensation has no significant effect on employee performance and work discipline has a negative and significant effect on employee performance partially. Simultaneously, financial compensation and work discipline have a positive and significant effect on employee performance at PT. Indah International Logistics. The results of this study are expected to provide benefits for PT. Indah Logistik Internasional to improve employee performance through financial compensation and work discipline.